Law Reform of Insider Trading and Market Manipulation in Legal Offer (Go Public) Process - Yuli Prasetyo Adhi; Prasasti Dyah Nugraheni; Dewi Sulistianingsih; Diani Indah Rachmitasari; Amar Ma’ruf (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2025)
The initial legal offering process or Public Company is the process of offering various securities in the shape from various shares owned by the Company to investors. The process from selling various securities in the shape from various shares owned by the Company consists of the process from offering various securities in the shape from various shares for investors, the process from giving various securities in the shape from various shares, which have been adjusted by orders from investors, and the process of listing the various securities in the shape from shares that have been sold on the stock exchange. Besides, the stage of selling various securities in the shape from shares owned by the Company consists of the stage from initial pertaining to the preparatory process for the sale of various securities in the shape from shares owned by the Company, the stage of registration application pertaining to Capital Market Supervisory Agency as institution whose task is for regulate and supervise activities in the capital market sector, the stage from share offering pertaining to investors, and the stage of listing from shares pertaining to the stock exchange market an institution whose job is to trade various securities in the shape from various shares owned by a Company to investors. In writing this article, the author uses the normative-juridical research method, which is a research method that is carried out using various sources of library law or secondary sources of law to find solutions to existing legal problems.